Pengaruh Model Pembelajaran Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas XI IPA SMA Negeri 2 Palu - Aziza, Aziza; Djaeng, Maxinus; Amri, Baso (Mitra Sains, 2016)
This study aimed to describe the effect of learning model and learning motivation on studets’ learning achievements in mathematics. This research was conducted at SMAN 2 Palu using a quasi-experimental design with factorial 2 ´ 2. The independent variable in this study is learning model and learning motivation. The dependent variable is the students’ mathematics learning achievements. Instruments used in the form of learning motivation questionnaire and achievement test. These samples students of class XI-IPA taken using random sampling techniques. Analysis of data using analysis of variance two-lane. Results showed (1) there is a significant difference the mathematics learning achievements of students between who are taught trough active learning model and direct learning; (2) there is a significant difference the mathematics learning achievements of students beetween high learning motivation and student learning achievements learning motivation is low; (3) there is an interaction between learning active learning model and learning motivation of students; (4) specifically for low motivation students who are taught by active learning model mathematics learning achievements was higher than students taught with direct learning; (5) specifically for high motivation students who are taught by active learning model mathematics learning achievements was lower than students taught with direct learning; (6) specifically for active learning model students who have high motivation to mathematics learning achievements higher than the students who have low motivation, and (7) specifically for direct learning model students who have high motivation to mathematics learning achievements higher than the students who have low motivation.